Pengembangan Alat Ukur Budaya Organisasi Pada Kontingen Garuda Pasukan Perdamaian PBB - Muhammad Eko Heru Saputro; Anissa Lestari Kadiyono (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2024)
Developments in science and technology that occur in the world bring changes to human life. The change will ultimately bring higher tension to each individual. In order for organizational goals to be carried out properly, support from management is needed. This study aims to examine the extent to which the validity and reliability of Organizational Culture. The impact on personnel carrying out assignments to UN peacekeeping forces, so they can provide an overview and input to the organization in build its organizational culture, to increase success in assignments. The process includes completing the construct of measuring instrument by reducing the dimensions to a number of indicators, creating items that represent indicators from each existing dimension, and conducting an expert review. Furthermore, the researchers collected data using online questionnaire, on a sample of the assignment unit with a total sample of 125 people consisting of various positions. This research was tested with a high Chronbach's Alpha value, so it can be said that the organizational culture measuring instrument has ideal reliability. From the results of calculating Item Response Theory, it is obtained proportion at a good value, it can be said that the item is suitable for use. The results of the confirmatory factor analysis show the relationship between dimensions of Organizational Culture meets the requirements, for model fit and factor loading values ​​of Organizational Culture can be said to be good. Thus the measuring instrument of organizational culture is reliable and valid to use.